FC002SERUM URIC ACID AND KIDNEY DISEASE MEASURES INDEPENDENTLY PREDICT CARDIOVASCULAR AND TOTAL MORTALITY: THE URIC ACID RIGHT HEART HEALTH (URRAH) PROJECT. (29th May 2021) - Viazzi, Francesca; Russo, Elisa; Leoncini, Giovanna; Pontremoli, Roberto; Borghi, Claudio; (SIIA), on behalf of the Working Group on Uric Acid; Cardiovascular Risk of the Italian Society of Hypertension
Abstract: Background and Aims: Serum uric acid may predict the onset and progression of kidney disease, and the occurrence of cardiovascular (CVM) and all-cause mortality (ACM). Nevertheless, it is unclear which is the appropriate definition of hyperuricemia in presence of chronic kidney disease and whether HU and renal impairment are independent risk factor for mortality. Our goal was to study the relationship between uric acid and chronic kidney disease in causing mortality. Method: We retrospectively investigated a total of 21, 963 patients from the URRAH study database for whom data about cardiovascular and all-cause mortality were available. Hyperuricemia was defined on the basis of the outcome specific cut-off separately identified by ROC curves according to eGFR strata. The primary endpoints were ACM and CVM, composite of the occurrence of fatal heart failure and fatal cerebrovascular and cardiac events. We calculated the hazard ratios for eGFR, serum uric acid, albuminuria, and their combination. Results: After a 9.8 -year follow-up, there were 1, 582 (7.20%) cardiovascular events and 3, 130 (14.25%) deaths for all causes. The incidence of CVM and ACM increased in parallel with reduction of eGFR strata and with progressively higher uric acid quartiles. During 215, 618 person-years of follow-up, the incidence rate for CVM, stratified on the basis of eGFR (>90, between 60 and 90 and <60 ml/min) was significantly higher in patients with HU and albuminuria (3.8, 22.1 and 19.1, respectively) as compared to those with only one risk factor or none (0.4, 2.8 and 3.1, respectively, Figure 1 ). Serum uric acid and eGFR significantly interact in determining cardiovascular and all-cause mortality. For each SUA increase of 1 mg/dl the risk for CVM and ACM increased by 10% even after adjustment for potential confounding factors included eGFR and the presence of albuminuria (Figure 2 ). Conclusion: Hyperuricemia is a risk factor for cardiovascular and all-cause mortality additively to eGFR strata and albuminuria, in patients at CV risk.